UPAYA MENJADI SOSOK GURU PENDIDIKAN KEWARGANEGARAAN YANG PROFESIONAL BAGI GENERASI Z - Kusnadi; Areta, Canda Cicilia; Purwatiningsih, Ary (Prosiding Temu Ilmiah Nasional Guru, 2023)
This study aims to analyze the efforts that civics education teachers can make tobecome influential professionals in shaping Generation Z is committed to citizenship and activelyparticipates in the life of the nation and state. The research method used is a literature review thatintegrates various sources relevant to civics education, teacher professionalism, and thecharacteristics of Generation Z. The results show that efforts to become a professional civicseducation teacher for Generation Z require an in-depth understanding of the characteristics ofgeneration Z, including different learning preferences and their exposure to technology. Teachersneed to develop innovative teaching approaches, involve technology as an effective tool, anddesign lessons that are relevant to contemporary social and political situations. Teachers mustalso develop strong moral and ethical leadership competencies to become role models forGeneration Z regarding citizenship attitudes, behaviors, and values. Continuous professionaltraining and development is also the key to improving the quality of civics education teachers. Inimplementing the "Freedom to Learn" concept, teachers must encourage Generation Z toparticipate actively in their learning process. This can be achieved through collaborativeapproaches, research projects, and opportunities to take initiative in understanding complexcitizenship issues.